2019
DOI: 10.1161/hypertensionaha.119.13155
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Plays a Central Role to Modulate the Plasma and Fecal Metabolomes in Response to Angiotensin II

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 43 publications
(48 reference statements)
9
60
0
Order By: Relevance
“…Low blood calcium may stimulate renin release and consequently increase the levels of angiotensin II and aldosterone [6], which are responsible for regulating BP. Recent studies revealed that angiotensin II-induced HTN is associated with gut microbial composition and metabolites [7,8].…”
mentioning
confidence: 99%
“…Low blood calcium may stimulate renin release and consequently increase the levels of angiotensin II and aldosterone [6], which are responsible for regulating BP. Recent studies revealed that angiotensin II-induced HTN is associated with gut microbial composition and metabolites [7,8].…”
mentioning
confidence: 99%
“…However, some of these compounds were nearly undetected in GF mice implying that they are dependent on the gut microbiota and that gut microbial production is downregulated with Ang II treatment. Interestingly, the authors noted that several of the metabolites measured in Conv and GF animals were different between sexes [35]. Also, it was found that the gut microbiota from specific pathogen-free and non-obese diabetic male mice protected the immature female recipients from type 1 diabetes by altering gut microbiota, elevating testosterone, reducing islet inflammation and autoantibody production [36].…”
Section: Discussionmentioning
confidence: 99%
“…Shannon's index was used as α-diversity metric and computed using mothur (v 1.43.0) (Schloss et al, 2009). Bray-Curtis dissimilarity was used as ÎČ-diversity metric and computed using vegdist of the vegan package in R. The mouse fecal microbiome data were from Cheema et al (2019). The human fecal microbiome data were 16S rRNA data from 106 healthy individuals (Shagam et al, in preparation).…”
Section: Computing Nucleotide Diversities Nucleotide Diversities Betmentioning
confidence: 99%